Implementasi Akuntabilitas Pelaporan Keuangan sebagai Upaya Peningkatan Transparansi dan Kepercayaan Publik pada PT Bank Jatim - Widad, Naswa Faqrizah Al; Nawangsari, Ajeng Tita (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
This study investigates the implementation of financial reporting accountability at PT Bank Pembangunan Daerah Jawa Timur Tbk (Bank Jatim) as a strategic effort to enhance transparency and strengthen public trust. Accountability in financial reporting is a critical component of good corporate governance, particularly in the banking sector, where public confidence is an intangible but essential asset. The research employs a qualitative descriptive method with a case study approach. Data were collected from annual reports (2020-2023), Financial Services Authority (OJK) regulations, PSAK standards, and in-depth interviews with both internal stakeholders and customers. The findings reveal that Bank Jatim consistently complies with PSAK and OJK regulations, supported by layered internal and external audits. Transparency is achieved through detailed disclosures in annual reports and digital publications, although public understanding of financial statements remains limited. This study highlights that accountability not only fulfills regulatory obligations but also strengthens institutional legitimacy and public trust. The novelty of this research lies in its focus on a regional development bank, demonstrating that robust financial accountability practices can play a pivotal role in balancing transparency with customer data protection while sustaining public confidence in the regional banking sector.